Erratum to: Exploring the use of cactus Opuntia ficus indica in the biocoagulation–flocculation of Pb(II) ions from wastewaters - T. Nharingo; M. T. Zivurawa; U. Guyo (Springer, 2023)
Erratum to: Int. J. Environ. Sci. Technol. DOI 10.1007/s13762-015-0815-0 The original publication of this article unfortunately con- tained two mistakes. At the end of the Introduction and in the Acknowledgments unfortunately the text ‘‘(removed for the purpose of blinding the manuscript)’’ has not been replaced by ‘‘Midlands State University’’.